Family law in contemporary Iran : women's rights activism and Shari'a - Bøe, Marianne, 1977- (International library of Iranian studies, 2015)
"Passed into law over a decade before the Iranian Revolution, the Family Protection Law drew the ire of the conservative clergy and the Ayatollah Khomeini, and was one of the first laws to be rescinded following the establishment of the Islamic Republic. The law was hardly a surprising target, however, since women's status in Iran was then - and continues now to be - a central concern of Iranian political leaders, media commentators and international observers alike. Examining the issue of women's status in a modern context, Marianne Bøe offers a nuanced view of how women's rights activists assert their positions within an Islamic context. By weaving together religious and historical texts and narratives with discourses on human rights, these women were able to communicate their views to those in political power. In 2007, after a 40-year hiatus, codified family law stormed back onto the Iranian political scene with the introduction of the Family Protection Bill. However, the dynamics in 2007 were considerably different from those of 1967. Whereas the earlier law attempted to grant women a wider range of rights in marriage and divorce, the 2007 Bill restricted women more than the laws then on the books. As a result, the Bill proved a massive point of contention and was, at one point, withdrawn from consideration due to overwhelming opposition. It has since been resubmitted though the most controversial elements of the Bill and family law in general continue to be debated. By examining women's rights activists, Bøe emphasises the ways in which these women's elaborations on family law entail both change and continuity of the Islamic theology, and particularly how different secular and religious-based sources intersect and are entwined. Through her substantial fieldwork and innovative analysis, Bøe undermines the traditional view of 'Islamic Feminism' as monolithic and clears a path to a new understanding of the role of women's rights activists in shaping and synthesising debates on the Shariʻa, women's rights and family law. As such, this book is essential for anyone studying family law and the role of women in contemporary Iran"--Unedited summary from book jacket